The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.12968/jowc.2012.21.4.190
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane reduces wound size in early stages of the healing process

Abstract: This study was financially supported by the Competitive Research Funding of the Tampere University Hospital (Grant 9H041, 9J047). The authors have no additional conflicts of interest to declare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In one week period ,there was no statistically significant variation in reepithelialization between groups but the degree of reepithelialization of wounds cover by amniotic membrane were better Figure ( This result agreed with comparative study of Nordback etal., they concluded that the epithelialization was somewhat larger in the AM group on days 7 but the difference was not statistically significant (17). In two weeks period, There was a statistically significant enhancement of epithelialization of amniotic membrane group compared to control group as in Figure ( The amniotic membrane has beneficial reepithelialization effects, the AM contains many growth factors and the basement membrane facilitates migration of epithelial cells which reinforces the adhesion of basal epithelial cells, and may promote epithelial differentiation ,the AM provides a suitable substrate, such as laminins for rapid attachment of epithelial cells.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In one week period ,there was no statistically significant variation in reepithelialization between groups but the degree of reepithelialization of wounds cover by amniotic membrane were better Figure ( This result agreed with comparative study of Nordback etal., they concluded that the epithelialization was somewhat larger in the AM group on days 7 but the difference was not statistically significant (17). In two weeks period, There was a statistically significant enhancement of epithelialization of amniotic membrane group compared to control group as in Figure ( The amniotic membrane has beneficial reepithelialization effects, the AM contains many growth factors and the basement membrane facilitates migration of epithelial cells which reinforces the adhesion of basal epithelial cells, and may promote epithelial differentiation ,the AM provides a suitable substrate, such as laminins for rapid attachment of epithelial cells.…”
Section: Resultsmentioning
confidence: 93%
“…Nordback etal., found that the effect of AM decreases in later stages. they concluded that the difference in epitheliazation was not statistically significant between the dispase de-epithelialized, glycerol cryopreserved amniotic membrane group and sodium chloride-moistened gauze group at 21 day period (17) .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…After that, the other evaluations occurred at three-day intervals, that is, on days 3, 6, 9, 12, 15, 18 and 21. The animals received no treatment on postoperative day 21, but the wound condition was evaluated, and they were then anesthetized and euthanized [14]. The measurement of the wound area was performed by tracing the perimeter of the wound using a sterile polypropylene film placed over the wound and the borders of the wound were traced using a fine-tip brush and indelible ink.…”
Section: Methodsmentioning
confidence: 99%